Evaluation of Patients with Hypocalcemia in Pediatric Emergency Department - Çevik, Seda; Özçelik Kartal, Özge; Bezen, Diğdem; Kaçar, Alper (Cerrahpaşa Medical Journal, 2024)
Objective: We aimed to evaluate the demographic, clinical, and laboratory findings of patients who presented to the pediatric emergency outpatient clinic of our hospital and whose tests revealed hypocalcaemia, and to determine whether the coronavirus disease 2019 pandemic affected the frequency of hypocalcemia. Methods: Between 1 March 2019 and 1 March 2021, the gender, age, gestational age, gestational week, birth weight, history of comorbidities, presenting complaint, physical examination findings, diet, duration of breastfeeding, duration of vitamin D intake were recorded in patients aged 0-18 years who presented with various complaints and were found to have hypocalcemia. All data were divided into two periods as pre-pandemic and pandemic period and compared within themselves. Results: The mean age of the 35 patients in the study was 6.3 years and 18 of them were male. The rate of regular and adequate vitamin D use was 22.86%. In etiological diagnoses, vitamin D insufficiency was 11.43% and vitamin D deficiency was 74.28%. When the etiological diagnoses were evaluated according to seasonal distribution before the pandemic and seasonal distribution after the pandemic, no significant difference was found in both groups. Conclusion: Vitamin D deficiency and insufficiency was found to be the most common etiological cause in patients with hypocalcemia in pediatric emergency department. The rate of regular and adequate use of vitamin D supplementation was also found to be low, and in order to increase this rate, it should be planned to increase compliance with the vitamin D supplementation program in primary health care institutions. Cite this article as: Çevik S, Özçelik Kartal Ö, Bezen D, Kaçar A. Evaluation of patients with hypocalcemia in pediatric emergency department. Cerrahpaşa Med J. 2024;48(3):228-232.